Estimating air travel-associated importations of dengue virus into Italy - Quam, Mikkel B.; Khan, Kamran; Sears, Jennifer; Hu, Wei; Rocklöv, Joacim; Wilder-Smith, Annelies (Journal of travel medicine, 2015)
AbstractBackground. Southern Europe is increasingly at risk for dengue emergence, given the seasonal presence of relevant mosquito vectors and suitable climati
Gesehen am 16.07.2020